DEVELOPMENT OF PIEZO DISC AS A THROAT MICROPHONE - Rupali Jadhav; Pawan Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper mainly focus on the development of piezodisc as a throat microphone.Piezoelectric materials become the most attractive functional materials for sensors because they can directly convert mechanical energy to electrical energy and vice versa. The throat mic separates the environmental noise from voice via a non-traditional method of sound induction through the vibrations of the throat. Due to the voice coming from the vibrations in the neck and not from the air, there is no extra background noise for the microphone to pick up. The throat microphone picks up the voice signals from the vibrations in the users’ neck, rather than from the air. They eliminate noises and allow the speaker to reach a larger audience more effectively by protecting the throat.